Election fraud : detecting and deterring electoral manipulation - Alvarez, R. Michael, 1964-; Hall, Thad E. (Thad Edward), 1968-; Hyde, Susan D. (Brookings Series on Election Administration and Reform., 2008)
"Brings together experts on election law, election administration, and U.S. and comparative politics to examine the U.S. understanding of election fraud. With survey data, incident reports, and state-collected fraud allegations, measures the extent and nature of election fraud in U.S. Analyzes techniques for detecting and potentially deterring fraud"--Provided by publisher